Prevalence of ear disease in cats undergoing cone beam computed tomography for dental procedures - Boothe, Hannah F.; Volker, Mary Krakowski; Tjepkema, Jennifer; Hespel, Adrien-Maxence (Frontiers in Veterinary Science, 2025)
IntroductionIn this prospective, cross-sectional study, 303 feline patients were evaluated via cone beam computed tomography (CBCT) for evidence of incidental ear disease during a dental procedure.MethodsAll feline patients over one year of age presenting to a private practice veterinary dentistry and oral surgery specialty clinic underwent CBCT imaging which included the oral cavity and ear canals. The following were recorded if present: periodontal disease, tooth resorption and/or ear disease.ResultsEar disease was diagnosed as an incidental finding in 41.4% of cats that were imaged; this is higher than previously reported prevalence studies of the general feline population ranging from 2-19%. Periodontal disease and tooth resorption were not significantly associated with ear disease. However, cats less than or equal to 10 pounds were found to be at higher risk of ear disease.DiscussionThis study highlights the importance of advanced imaging in the diagnosis of not only dental disease but also ear disease in cats.